Expression et narration de la vulnérabilité en santé : des modes de donation à l'intégration biographique - Hervé Breton
The object of this article is to apprehend the experience of vulnerability in health by soliciting expression from the point of view of the subject who experiences it. The method used will be "radically" in the first person perspective, since it will proceed from a narrative work based on the author's lived experience. The aim is thus to apprehend vulnerability in health by examining the ways in which the experience of illness can be expressed, finds ways of expression, and is carried out in different forms of narrative. By presenting three types of narratives - the narrative of a period of life, the narrative of a moment, and the phenomenological description of a moment - the article provides a concrete grasp of the experiential and biographical dimensions experienced during pzriod of life in which the person experiences vulnerability. The aim of this research is to clarify the contributions of biographical narratives, the narration of experiences and micro-phenomenological description to support the process of recognising and understanding the experience of vulnerability in education and health.